2017
DOI: 10.3329/baj.v20i1.34877
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Levels and Weed Management on Yield Performance of BRRI Hybrid Dhan3 Under AWD Irrigation System

Abstract: Experiment was carried out at the Agronomy field of Bangladesh Rice Research Institute, Gazipur, during the period from December 2014 to May 2015 to investigate the response of different levels of N and methods of weeding on weed abundance and grain yield of BRRI hybrid dhan3 under alternate wetting and drying (AWD) irrigation condition. The treatments consisted of five N levels viz.,0, 60, 120,180 and 240 kg N ha -1 and four different weed control methods viz., Pre-emergence herbicide followed by 1HW, Pre-eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Smart technology such as location-specific variety, profitable cropping sequences, innovative cultural management, and appropriate agronomic management with smart dissemination using multiple means would maximize rice yield and minimize production barriers of rice. It is observed from different experimental results that rice yield could be increased by 0.74 t ha -1 by adopting proper agronomic management (Bhuiyan et al, 2017). Site-specific nutrient management improved productivity and profitability in rainfed lowlands of the Philippines and get 6% more yield and reduce nitrogen use in the farmers' field (Banayo et al,2018).…”
Section: Site-specific and Season Wise Agronomic Managementmentioning
confidence: 99%
“…Smart technology such as location-specific variety, profitable cropping sequences, innovative cultural management, and appropriate agronomic management with smart dissemination using multiple means would maximize rice yield and minimize production barriers of rice. It is observed from different experimental results that rice yield could be increased by 0.74 t ha -1 by adopting proper agronomic management (Bhuiyan et al, 2017). Site-specific nutrient management improved productivity and profitability in rainfed lowlands of the Philippines and get 6% more yield and reduce nitrogen use in the farmers' field (Banayo et al,2018).…”
Section: Site-specific and Season Wise Agronomic Managementmentioning
confidence: 99%
“…It was evident from the study that pre planting herbicide Authority 48 SC @ 200 ml ha -1 and 250 ml ha -1 found effective for controlling weeds than other doses of that herbicide. Bhuiyan et al, 2017 reported that different groups of herbicides controlled more than 80% of weeds in different nitrogen management practices in hybrid rice.…”
Section: Weed Control Efficiency (Wce)mentioning
confidence: 99%
“…Many studies have shown that saturated soil conditions significantly increase the number of weed species, density and biomass compared with continuous flooding (Bhager et al, 1999; Mahajan et al, 2009). This is especially true for sedges and grass species (Bhuiyan et al, 2017; Hill et al, 2001). Maintaining soil saturation at the early stage (pre‐sowing to 2–3 leaf stage) in direct‐seeded rice also resulted in the largest weed seed banks, especially in sedges, grasses and some upland weeds (Chen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%